ANALISIS LITERASI SAINS SISWA SMP DALAM PEMBELAJARAN IPA TERPADU PADA TEMA EFEK RUMAH KACA - Marta, Febrian Andi (2012)
Science literacy is important to be mastered by learners in relation to the way that students can understand the environment, health, science issues and other problems faced by modern society that relies heavily on technology and progress, as well as the development of science. PISA 2006 science literacy divide into four domains namely, the domain context, content, competencies and attitudes. Related to this, science literacy learners in Indonesia is still low, students in Indonesia is only at the level of the lowest measurement of PISA, which can only explain simple concepts. Integrated science is used as a learning model that fosters students' science literacy because literacy accords with the meaning of science itself. The theme of the Integrated science learning is the greenhouse effect, because during the many students who do not understand the concept of a greenhouse. This study uses descriptive analytical study using the ones shot case study design. Where the study did not conduct initial tests but directly at the end of the lesson and then given a test to determine students' science literacy profile. After doing research, the data that have been processed indicate that the science literacy of students domain content, context, and competence is being considered. For the students' attitudes toward science domain are also considered in the medium category. For further research could be more concerned about the use of local resources in the learning and grammar used in integrated science teaching materials using a language that is easily understood by students.